Gerontologia (geragogika) specjalna – obszar koniecznych badań i refleksji pedagogiki specjalnej. Wybrane zagadnienia - Chrzanowska, Iwona (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
In the text, an attempt was made to analyse selected issues related to gerontology in the relationship to people with disabilities. The context of analyses is the tendency of social ageing tendencies, observed in Poland and in the world, especially in European countries. Selected areas of reflection are combined with the conviction that there is a need for research which would fill in the gap in the field of research carried out so far, focused on the issue of the broadly defined life situation of the people with disabilities in the senior years, which is in the scientific merit of Polish special needs education (pedagogics). There is a justified fear that these individuals are more likely to experience marginalisation and exclusion in many areas of life than people of similar age in the general population.